Vocabulary learning for slow learner students in inclusive elementary schools: A case of Magetan Regency, East Java, Indonesia - Cahyono, Bambang; Asri, Dahlia; Trisnani, Rischa (Research Journal in Advanced Humanities, 2024)
This study aimed to describe and explain the conditions for learning vocabulary for slow learners in inclusive elementary schools. This research uses a descriptive-qualitative approach. Sampling was carried out on students with slow learners at 10 inclusive elementary schools in Magetan Regency, East Java, Indonesia, which were selected based on regional considerations. The data sources selected were 10 special accompanying teachers, vocabulary learning activities in class, and documents or archives related to slow learners. Data collection techniques include passive participant observation, in-depth interviews, and documentation. Data analysis uses an interactive analysis model, which is carried out through three activity flows: data reduction, data presentation, and drawing conclusions. The results of the study show that the vocabulary of slow learners is minimal when compared to that of other normal students. Slow-learner students have difficulty using vocabulary in reading and writing and are weak at stringing letters into words. Factors that hinder slow learners’ vocabulary mastery include being less accustomed to using Indonesian and the lack of support from parents. Teaching materials taught by the teacher include the introduction of new terms, synonyms, antonyms, and standard words, filling in gaps in sentences, and constructing sentences with the available words.